CDK4 inhibition restores G1-S arrest in MYCN-amplified neuroblastoma cells in the context of doxorubicin-induced DNA damage - Gogolin, Sina; Ehemann, Volker; Becker, Gabriele; Brückner, Lena Marie; Dreidax, Daniel; Bannert, Steffen; Nolte, Ingo; Savelyeva, Larissa; Bell, Emma; Westermann, Frank (Cell cycle, 2013)
Relapse with drug-resistant disease is the main cause of death in MYCN-amplified neuroblastoma patients. MYCN-amplified neuroblastoma cells in vitro are characterized by a failure to arrest at the G₁-S checkpoint after irradiation- or drug-induced DNA damage. We show that several MYCN-amplified cell lines harbor additional chromosomal aberrations targeting p53 and/or pRB pathway components, including CDK4/CCND1/MDM2 amplifications, p16INK4A/p14ARF deletions or TP53 mutations. Cells with these additional aberrations undergo significantly lower levels of cell death after doxorubicin treatment compared with MYCN-amplified cells, with no additional mutations in these pathways. In MYCN-amplified cells CDK4 expression is elevated, increasing the competition between CDK4 and CDK2 for binding p21. This results in insufficient p21 to inhibit CDK2, leading to high CDK4 and CDK2 kinase activity upon doxorubicin treatment. CDK4 inhibition by siRNAs, selective small compounds or p19INK4D overexpression partly restored G₁-S arrest, delayed S-phase progression and reduced cell viability upon doxorubicin treatment. Our results suggest a specific function of p19INK4D, but not p16INK4A, in sensitizing MYCN-amplified cells with a functional p53 pathway to doxorubicin-induced cell death. In summary, the CDK4/cyclin D-pRB axis is altered in MYCN-amplified cells to evade a G₁-S arrest after doxorubicin-induced DNA damage. Additional chromosomal aberrations affecting the p53-p21 and CDK4-pRB axes compound the effects of MYCN on the G₁ checkpoint and reduce sensitivity to cell death after doxorubicin treatment. CDK4 inhibition partly restores G₁-S arrest and sensitizes cells to doxorubicin-mediated cell death in MYCN-amplified cells with an intact p53 pathway.
Gesehen am 12.02.2020
Im Titel ist die Zahl "1" tiefgestellt